Toleransi Beragama Menurut Perspektif Al Quran - Siti Aminah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
The Qur'an explicitly forbids a person to impose his religion let alone in the midst of a pluralistic society such as Indonesia. Awareness and belief in the truth of Islam is not shown through practices of violence, coercion but rather awareness with demonstrated tangible evidence of the truth. Therefore, the nature of a source of guidance around the globe created by God if it is not hindered by the acts or behavior that is not good, it will be moving towards recognition and strengthen user confidence through revelation. More importantly, the nature of human beings assign responsibility in observing the commandments of universal guidance, which requires an act of free will to guide the nature of the strong state. Although agreed on should not be any compulsion in religion but commentators disagree about who should not be forced and that should be forced. For At-Tabari, who should not be forced out of the verse is the People of the Book (Jews, Christians) as long as they pay the jizya (poll tax).Keywords: Tolerance, Religion, Islamic Perspective.